STRATEGI BERTUTUR PEDAGANG SEMBAKO DUSUN POLAGA KECAMATAN SIKAKAP KABUPATEN KEPULAUAN MENTAWAI - Sababalat, Retin; Sari, Asri Wahyuni; Pebriani, Yulia (PBSI, FKIP UNISSULA, Semarang, 2021)
This research was motivated by the various types of tribes that exist in traditional markets in Polaga hamlet, Sikakap District. This study aims to describe the form of the telling strategy of the foodstuff traders in Polaga Hamlet, Sikakap District, Mentawai Islands Regency. This type of research is qualitative research using descriptive methods. The data source of this research is the groceries traders in the traditional market of Polaga Hamlet, Sikakap District. The results of the data analysis show that the strategy of telling the groceries in Polga Hamlet, Sikakap District, Mentawai Islands Regency is as follows. First, a straightforward, no-nonsense strategy, which is used to clearly address buyers without any sweet words. Second, the strategy of speaking with positive courtesy, the trader gives a speech that is both confident and optimistic to the buyer to want to buy semabko in his shop. Third, the strategy of speaking with negative politeness, namely traders using speech that makes the buyer feel uncomfortable with the speech delivered by the trader. Fourth, the strategy is to speak vaguely, in which traders use speech that uses community language to the buyer.